IMPLEMENTATION OF MONOPOLY BOARD GAME TO IMPROVE LEARNING OUTCOMES OF 6TH GRADE ELEMENTARY SCHOOL STUDENTS: - - Lulu' Arifatun Munasiroh Lulu' (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Learning Indonesian Language in elementary schools requires students to develop critical and creative thinking skills as well as an understanding of abstract linguistic concepts such as majas or figurative language. However, sixth-grade students often experience difficulties in mastering various types of majas due to the use of conventional teaching methods and the limited utilization of engaging learning media. These challenges result in low motivation, participation, and learning score. The aim of this study is to examine the implementation of the Monopoly Majas learning media to enhance the learning activities and outcomes of students of sixth-grade in Indonesian Language lessons. The research used a Classroom Action Research (CAR) method using the Kemmis and McTaggart model, consists of: planning, action implementation, observation, and reflection. The research involved 21 students of sixth-grade at Nasima Primary School. Data were collected through observation, interviews, and achievement tests. The results showed that the use of Monopoly Majas significantly improved students’ learning activities and outcomes. The percentage of active participation increased from 67% in the pre-cycle to 81% in the first cycle and 90% in the second cycle. Similarly, the students’ average learning achievement score increased from 65 in the pre-cycle to 78 in the first cycle and 89 in the second cycle. Therefore, the use of Monopoly Majas as a learning medium proved effective in enhancing students’ motivation, engagement, and achievement in understanding figurative language in Indonesian Language learning for sixth-grade elementary students.